The Facebook Sabbatical as a Cycle: Describing the Gendered Experience of Young Adults as They Navigate Disconnection and Reconnection. (September 2018) - Franks, Jessica; Chenhall, Richard; Keogh, Louise
Young adults are known to adopt Facebook (FB) sabbaticals as a coping strategy for FB-induced technostress, which are often linked to problematic overuse habits. Yet, there has been little investigation of how young adults experience, navigate, and negotiate FB sabbaticals and the impact this has on their social connections and overall well-being. To address this, we conducted a qualitative study of six young adults, aged 18–34 to understand their FB sabbatical experiences, how they negotiated their social connections during their sabbatical and sough to explain the reasons associated with their return to FB. We propose a FB sabbatical support model and offer three research propositions. Our results suggest that (1) FB sabbaticals are of benefit in addressing unhealthy FB habits, yet key supportive factors vary in value of importance and influence between genders; and (2) despite young adults' efforts to mitigate technostress via FB sabbaticals, this strategy presented multiple challenges that affected their online and offline connections and personal health and well-being in positive and negative ways, contributing to cyclic habits of FB discontinuation and reconnection.